Molecular diagnostic markers of Tachysurus fulvidraco and Leiocassis longirostris and their hybrids - Liang, Hongwei (Springerplus, 2016)
BACKGROUND: Bagridae is an important family of catfishes and has a high market demand. Recently, more cultivable Bagridae fishes are being exploited in China, and hybridization of some species has been carried out to achieve better growth performance, favorable sex ratios and better disease resistance. Yet, these hybrids have further increased the difficulties of taxonomy identification due to morphological indistinguishableness. RESULTS: In this study, the molecular identification technologies for Tachysurus fulvidraco, Leiocassis longirostris sand their hybrids were successfully established by using mitochondrial COI and nuclear ITS sequences to identify the maternal and paternal lineage, respectively. CONCLUSION: These molecular diagnostic methods could also be used to manage breeding plans of hybrids, monitor and minimize the negative impacts of hybridization programs in aquaculture. Furthermore, our study could also provide a reference for establishing detection technique for hybrids in other groups of fishes.